A prospective study of 50 cases of laparoscopic intestinal anastomosis by Endo GIA universal loading stapler (green/blue) versus Endo GIA articulating reload with tri staple technology (purple) - Vasaiya, Mehulkumar K.; Shah, Samir M.; Gohil, Vikram B.; Vaghasia, Milankumar S. (International Surgery Journal, 2020)
Background: Intestinal anastomosis is a commonly performed procedure in surgery. Various evolvements have occurred in the field of intestinal anastomosis and recent advancement is the use of stapler in laparoscopic surgeries as a device for Gastrointestinal (GI) anastomosis. Few previous studies evaluating the clinical safety of the 2 laparoscopic linear stapling devices are available. Methods: A prospective comparative study of 50 cases which met the inclusion and exclusion criteria were included in this hospital-based study. They were randomly allocated to two groups, Group A which underwent laparoscopic intestinal anastomosis by Endo GIA tri-staple (purple) stapler and Group B which underwent Endo GIA universal loading unit (blue/green) stapler. Primary outcome was assessed in terms of intra-operative staple line bleeding, operative time and post-operative anastomotic leak. Results: Patients with laparoscopic intestinal anastomosis by Endo GIA tri-staple stapler (purple) have required less operation time as compared to Endo GIA universal loading unit. In Endo GIA universal loading unit (blue/green) 04% patients developed anastomotic leak and 40% patients had intra-operative staple line bleed while with Endo GIA tri-staple no postoperative anastomotic leak was found and 02% patients developed intra-operative staple line bleeding. Conclusions: The result of our study has shown that the Endo GIA reload tri- staple (purple) is superior in terms of having no anastomosis leak, negligent staple line bleeding and less operation time as compared with Endo GIA universal loading unit (blue/green). Thus, laparoscopic intestinal anastomosis by Endo GIA reload tri-staple stapler (purple) technology is more effective and overall more efficient.